NK cell-specific knockout of UTX modulates pulmonary metastasis of melanoma in a sex-dependent manner - HUANG Pei; WANG Hongchen; HUANG He (陆军军医大学学报)
Objective‍　‍To explore the role of X chromosome encoded epigenetic regulator UTX in NK cell-mediated anti-tumor activity. Methods‍　‍Male Ncr1-iCre mice were crossed with female UTXfl/fl mice to generate F1 Ncr1-iCre+UTXfl/- male mice, which were further crossed with female UTXfl/fl mice to obtain male Ncr1-iCre-UTX fl/-control mice (M-Con) and NK-specific deletion of UTX male mice Ncr1-iCre+UTXfl/- (M-KO), as well as female Ncr1-iCre-UTXfl/fl control mice (F-Con) and UTX-deficient female mice Ncr1-iCre+UTXfl/fl (F-KO). UTX-deficient mice were injected with melanoma cell line B16F10 via tail vein to observe pulmonary metastatic tumor nodules. Moreover, flow cytometry was applied to detect the proportion and quantity of pulmonary NK cells (CD3-CD19-NK1.1+), maturation makers KLRG1 and CD11b, activation receptors NKG2D and CD69, and effector molecules, including perforin, granzyme B, CD107a, and IFN-γ. Then pulmonary NK cells were sorted and co-cultured with B16F10 cells, and the apoptosis of the melanoma cells was measured with flow cytometry. Results‍　‍Compared with the M-Con mice, the M-KO mice presented less number of pulmonary tumor nodules (P<0.05), increased proportion and quantity of NK cells in the tumor microenvironment (P<0.01), though no obvious changes in the ratio of NK maturation makers KLRG1 to CD11b, enhanced expression level of cytotoxic molecule perforin (P<0.01), but no changes in the expression of effector molecule granzyme B, degranulation marker CD107a and cytokine IFN-γ in NK cells. Co-culture of NK cells and B16F10 cells promoted the apoptosis of tumor cells (P<0.05). Compared with the F-Con mice, the F-KO mice had no statistical difference in the number of pulmonary tumor nodules, but larger proportion and number of NK cells (P<0.05), decreased ratio of KLRG1 to CD11b (P<0.01), elevated level of perforin but decreased levels of granzyme B, CD107a and IFN-γ in NK cells (P<0.01). The co-culture of NK cells and B16F10 cells reduced the apoptosis of tumor cells in F-KO female mice (P<0.05). Conclusion‍　‍NK-specific deletion of UTX regulates pulmonary metastasis of melanoma in a sex-dependent manner.